849. PLATYSTELE OVATILABIA: Orchidaceae. (December 2016) - Dodsworth, Steven
Summary: Platystele ovatilabia (Ames & C. Schweinf.) Garay is illustrated, as the second of two Platystele species. The history, taxonomy and phylogenetic relationships of Platystele are discussed further.